Profil Kesiapan Siswa pada Pembelajaran Biologi Berbasis Deep Learning Berdasarkan Self-Regulation dan Critical Thinking di Kelas X SMA - Dina Alfiyana; Muhammad Syaipul Hayat; Praptining Rahayu (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2026)
This study aimed to determine the readiness and thinking habits of students, namely self-regulation and critical thinking in facing biology learning based on deep learning. The study was conducted using descriptive qualitative - quantitative methods, namely data collection with questionnaire results and observations during the learning process supported by the results of student answers through interviews. Participants in this study were 103 students of class X digital media at SMA Islam Sultan Agung 1 Semarang who received biology subjects on environmental change. The results of the study were collected through a habits of mind questionnaire with a score of 81 in the very good category. The observation results showed that students' habits of mind scored 71.53 in the good category and deep learning data scored 54.19 in the sufficient category. Strengthened by interview data, habits of mind were already good although not optimal, but in deep learning data still need optimization even though some have been implemented. Thus, the habits of mind of class X students of SMA Islam Sultan Agung 1 Semarang need to be improved to support the implementation of deep learning learning which is still not optimal in its preparation. Keyword: Biology Learning, Critical Thinking, Deep learning, Self-Regulation